Pelatihan dan Pendampingan Pemanfaatan Biopestisida Metil Eugenol Bagi Petani Lombok di Kampung Walma Distrik Skanto Keerom Papua - Bambang Suhartawan; Syarifuddin Syarifuddin; Herman HI Tjolleng Taba; Tanwir Tanwir; Mugiati Mugiati; Daawia Daawia; Supeni Sufaati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Fruit flies are the main pests causing decreased productivity of horticultural crops in Walma Village, Skanto District, Keerom Regency. This pest attack causes significant economic losses for local farmers with fruit damage rates reaching 40-60%. This community service activity aims to increase farmers' knowledge and skills in utilizing methyl eugenol pheromones as environmentally friendly biopesticides to control fruit flies. Implementation methods include counseling on fruit fly biology and pheromone mechanisms, training on making pheromone traps using local materials, demonstration of trap installation in fields, and continuous assistance during three months of planting season. This activity involved 35 farmers from Walma Village who own horticultural land. The results showed an increase in farmers' knowledge by 78% from pre-test to post-test, successful installation of 140 pheromone trap units in 15 hectares of land, reduction in fruit fly attack rates from 45% to 18%, and increase in harvest yields by 35-42%. Farmers also showed high enthusiasm with commitment to continue using this biopesticide. This activity makes a real contribution to increasing sustainable agricultural productivity and reducing chemical pesticide use in Papua region, specifically Keerom Regency.